Knowledge, Self-Efficacy, and Preventive Behavior of COVID-19 Outbreak Among Community in Malaysia - Normaliza Binti Ab Malik; Rusyda Helma Mohd; Nor Ba’yah Abdul Kadir (SAGE Publishing, 2024)
Indexed by WOS/SCOPUS/ERA